Organizational Leadership in Accelerating Digital Transformation - Nazmah; Yani, Achmad; Sari, Dian Purnama (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
In the research, the focus is on organizations that have transitioned towards digitization across Indonesia. Managing organizational resources is key to understanding the shift from bureaucracy to digital, with the leader's role crucial in optimizing organizational effectiveness. Human resource development emphasizes viewing individuals as assets. This study involves all employees of Public Body X as samples, using a purposive sampling approach. In the context of Indonesia's government digitization policy, institutions already have digital platforms to enhance transparency. The article highlights challenges such as resistance to change, especially within robust bureaucratic structures, underscoring the importance of leaders being flexible and responsive to change demands. Looking ahead, the article emphasizes the significance of leaders with a growth mindset to comprehend and develop their potential in the digital era. Transformation towards a more agile digital system requires innovative strategies and the willingness of organizational members to undergo comprehensive change. In conclusion, leaders understanding digital dynamics can drive organizational effectiveness and efficiency while addressing challenges in the digital era.